Evaluation of Spanish journals: steps towards a system that measures openness and internationality - Rodríguez-Yunta, Luis (Anuario ThinkEPI, 2015)
This paper has as its starting point the premise that it is useful for the Spanish research ecosystem to have consolidated, open journals with international influence. Evaluation of journals is important because of the role of publications in establishing research credentials. Features required to achieve a balanced and fair evaluation system are described. The tools currently available to this purpose in Spain have major limitations. A proposal based on the ISOC database is presented, providing new assessment criteria that combine the trajectory or track record, openness and internationality of the Spanish humanities and social sciences academic journals.